2021
DOI: 10.17159/sajs.2021/7911
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating South African Weather Service information on Idai tropical cyclone and KwaZulu-Natal flood events (with corrigendum)

Abstract: Severe weather events associated with strong winds and flooding can cause fatalities, injuries and damage to property. Detailed and accurate weather forecasts that are issued and communicated timeously, and actioned upon, can reduce the impact of these events. The responsibility to provide such forecasts usually lies with government departments or state-owned entities; in South Africa that responsibility lies with the South African Weather Service (SAWS). SAWS is also a regional specialised meteorological cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Aside from material destruction, several aspects of repercussions from flood risk in -Western Africa include health impacts and economic losses [ 44 ]. The South-Eastern part of Africa has previously been hit by severe cyclones, exacerbating the COVID-19 disease and flooding damage [ 5 , 10 ]. Poor communities are defenceless due to the exposure of their livelihoods to flood impacts, particularly in rural locations with limited access to services and infrastructure [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from material destruction, several aspects of repercussions from flood risk in -Western Africa include health impacts and economic losses [ 44 ]. The South-Eastern part of Africa has previously been hit by severe cyclones, exacerbating the COVID-19 disease and flooding damage [ 5 , 10 ]. Poor communities are defenceless due to the exposure of their livelihoods to flood impacts, particularly in rural locations with limited access to services and infrastructure [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Research emphasizing the relationship between flood hazards and the impacts on the African continent is long-standing [ 5 , 17 , 26 , 32 , 33 , 37 ]. Wagner and others [ 44 ] did a systematic review of flood management in West Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Most of African countries are dependent on rain-fed agricultural activities and are vulnerable to climate extreme events that have detrimental socioeconomic impacts. Moreover, there is a need to develop temperature and rainfall prediction systems at S2S timescales in the African region, particularly to facility readiness for high-impact events such as flood events along the Mozambique coast (e.g., Tropical Cyclone Idai) and the eastern coast of South Africa as have happened in April 2019 (Bopape et al, 2021). Furthermore, it is imperative that governments in the region invest more resources in S2S prediction studies, particularly with the changing climate challenges that the world is facing.…”
Section: Southern Africamentioning
confidence: 99%
“…It is important for disaster management practitioners to learn from lessons in order to adapt good practices. This is the case with cyclone Idai that caused floods over Mozambique, Zimbabwe and Malawi resulting in hundreds of death and the KwaZulu-Natal (KZN) flood events soon afterwards causing death and destruction (Bopape et al, 2021). Research conducted by Bopape et al (2021) showed warnings of the events were given 2 and 1 day respectively and that there were shortcomings in locating the KZN floods indicating that the impacts experienced during the two events could have been minimized if long notices of the event were received.…”
Section: Literature Reviewmentioning
confidence: 99%